Kecerdasan Emosional sebagai Pemoderasi Pengaruh Kompetensi dan Indepedensi Pada Kinerja Auditor - Nova, Baiq Dewi; Latrini, Made Yenni (E-Jurnal Akuntansi; Vol 21 No 2 (2017), 2017)
Achieving good performance an auditor must have competency and independent attitude. In addition, the auditor must have emotional intelligence so that auditors work more optimum in carrying out auditing tasks where auditors who have better emotional intelligence will work more optimum than auditors who have intellectual intelligence. This study aims to determine the influence of competence and indepedence with emotional intelligence sebagia moderate on the performance of auditors in Public Accounting Firm in Bali Province.Teknik sampling technique used in this research is saturated sample technique with saturated sample method with the number of samples obtained as many as 32 samples. Data collection methods used in this study is to spread the questionnaire to the auditors at Public Accounting Firm. Data analysis technique used in this research is Moderated Regression Analysis (MRA). Based on the results of the research showed that emotional intelligence, competence and independence have a positive effect on auditor performance. Keywords:auditor performance, emotional intelligence, competence independence.